Regulation of Dissimilatory Sulfur Oxidation in the Purple Sulfur Bacterium Allochromatium Vinosum - Grimm, Frauke; Franz, Bettina; Dahl, Christiane (Frontiers in Microbiology, 2011)
In the purple sulfur bacterium Allochromatium vinosum, thiosulfate oxidation is strictly dependent on the presence of three periplasmic Sox proteins encoded by the soxBXAK and soxYZ genes. It is also well documented that proteins encoded in the dsr (dissimilatory sulfite reductase) operon, dsrABEFHCMKLJOPNRS, are essential for the oxidation of sulfur that is stored intracellularly as an obligatory intermediate during the oxidation of thiosulfate and sulfide. Until recently, detailed knowledge about the regulation of the sox genes was not available. We started to fill this gap and show that these genes are expressed on a low constitutive level in A. vinosum in the absence of reduced sulfur compounds. Thiosulfate and possibly sulfide lead to an induction of sox gene transcription. Additional translational regulation was not apparent. Regulation of soxXAK is probably performed by a two-component system consisting of a multisensor histidine kinase and a regulator with proposed di-guanylate cyclase activity. Previous work already provided some information about regulation of the dsr genes encoding the second important sulfur-oxidizing enzyme system in the purple sulfur bacterium. The expression of most dsr genes was found to be at a low basal level in the absence of reduced sulfur compounds and enhanced in the presence of sulfide. In the present work, we focused on the role of DsrS, a protein encoded by the last gene of the dsr locus in A. vinosum. Transcriptional and translational gene fusion experiments suggest a participation of DsrS in the post-transcriptional control of the dsr operon. Characterization of an A. vinosum ΔdsrS mutant showed that the monomeric cytoplasmic 41.1 kDa protein DsrS is important though not essential for the oxidation of sulfur stored in the intracellular sulfur globules.